Nietzsche's Pendulum: Oscillations of Humankind - Rapport, Nigel (The Australian journal of anthropology, 2005)
Oscillations have been famously treated by anthropologists at the level of social structure. Rites of passage: dynamic equilibrium: binary exchange. Employing a Nietzschean trope of the Apollonian and Dionysian, this article treats oscillations more existentially. Between cultural belonging and truth, between symbolic form and experience, between poetry and biology—the article disinters certain motilities of being and becoming that exemplify universals of human capacity and can be claimed to be ubiquitous in human experience. Tensions are intrinsic to the human condition, the article argues, and knowledge of the human is also to be found between: between the orderly and formal on the one hand, and the gratuitous, random and free on the other. For instance, in an oscillation between cultural belonging and scientific truth, Ernest Gellner acceded to knowledge of a possibly universal, rational morality. Oscillating between the psychically intensive methodology and the extensive, George Devereux advocated knowledge of the potentialities of the human psyche as such. Oscillating between ideal-typical, conceptual and symbolic schemata and the motile sensorium, between the biochemical conditioning of individual embodiment and the creative imagination, Edmund Leach and James Fernandez claimed knowledge of the connection between culture and society and bodily experience. Embracing oscillation one may approach an appropriately flexible and transitory knowledge of humankind, accepting the irony that it is ‘forms of movement’ that best give onto an appreciation of the human condition.